An Instrumental Assessment of Touch’n Go eWallet Mobile App - Hussain, Azham; Mkpojiogu, Emmanuel O.C.; Kamal, Fazillah Mohmad; Wahab, Rohazna binti; Che Meh, Noor Halawati (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study assessed the instrumentality of Touch ’n Go eWallet mobile app at selected areas in University Malaysia Perlis (UniMAP) and Politeknik Tuanku Syed Sirajuddin (PTSS) Perlis, Malaysia, in July and August 2019. Fifteen staff from the two institutions was selected as participants. The purpose of the test was to assess the usability of the app and get user feedback to improve the instrumental quality of the application in order to meet user satisfaction and their experience. This report contains the participants’ feedbacks, task completion rates, ease or difficulty of task completion, time on task, errors, and recommendations for improvements. This study used 4 tasks to assess the instrumental quality of Touch ‘n Go eWallet mobile app. Overall, the outcome of the study revealed that the app is generally usable and instrumental to assisting users accomplish their electronic wallet goals. There is however some observed issues in the app that require fixing to enhance the instrumental quality of app.